2008
DOI: 10.1038/labinvest.2008.95
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of iron regulatory genes in cirrhotic human livers: clues to the cause of hemosiderosis?

Abstract: Hepatic iron deposition unrelated to hereditary hemochromatosis occurs commonly in cirrhosis but the pathogenesis of this condition is unknown. The aim of this study was to compare the expression of genes involved in the regulation of iron metabolism in cirrhotic (n ¼ 22) and control human livers (n ¼ 5). Transcripts were quantitated by real-time RT-PCR and protein levels were assessed by western blot. Hepatic iron concentrations (HICs) were measured by a spectrophotometric method. Levels of hepcidin mRNA did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…26 HCV-positive samples obtained during routine patient work-ups were stained with hematoxylin and eosin (H & E) or Masson's trichrome and scored blindly for fibrosis and necroinflammatory activity using a METAVIR scoring system 27 as described previously. 28 Patients studied were designated HCV-positive if their serum tested positive in an enzyme-linked immunosorbent assay (EIA.3) for HCV antibodies.…”
Section: Materials and Methods Patients And Clinical Samplesmentioning
confidence: 99%
“…26 HCV-positive samples obtained during routine patient work-ups were stained with hematoxylin and eosin (H & E) or Masson's trichrome and scored blindly for fibrosis and necroinflammatory activity using a METAVIR scoring system 27 as described previously. 28 Patients studied were designated HCV-positive if their serum tested positive in an enzyme-linked immunosorbent assay (EIA.3) for HCV antibodies.…”
Section: Materials and Methods Patients And Clinical Samplesmentioning
confidence: 99%
“…9 Accumulation of iron in macrophages has been reported as an indicator of secondary iron overload status in CLD. 10 Down-regulation of circulating transferrin (Tf ) and its receptor has also been reported in liver cirrhosis (LC) patients, 11 which correlates with a raised Tf saturation index (%SAT). 12 We have recently reported on the significance of elevated serum ferritin levels in patients with decompensated CLD as a predictor of early mortality.…”
mentioning
confidence: 99%
“…Obstructive jaundice (OJ) increases the risk of liver injury and sepsis, leading to increased mortality [6,7,[11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…expression results more bacterial infections and mortality are higher, which confirms the importance of gp130 in innate immunity and IL-6 signaling.37 intrahepatic Stat3 activation predictable outcome, 38 and STAT3 knockout mice showed significantly higher death of widths after cecal ligation and puncture sepsis. Kano et al have shown that STAT3 signaling in the endothelium have anti-inflammatory as an important mediator of the endotoxin-induced inflammation [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation